Roadmap for searching cosmic rays correlated with the extraterrestrial neutrinos seen at IceCube - Carpio, JA (2017)
The authors gratefully acknowledge DGI-PUCP for financial support under Grant No. 2014-0064 as well as CONCYTEC for a graduate fellowship under Grant No. 012-2013-FONDECYT. The authors also want to thank Mauricio Bustamante and José Bellido for useful suggestions.